Description of Placoneis mologaensis, a new diatom from the Rybinsk reservoir on the Volga River, European Russia - Vishnyakov, Vasily S. (Phytotaxa, 2020)
A survey of surficial bottom sediments of the Rybinsk reservoir on the Volga, one of the largest and highly regulated rivers in Europe, revealed unknown species of the genus Placoneis. Detailed morphological observation using light and scanning electron microscopes allowed to describe this as P. mologaensis sp. nov. The species is characterized by linear-elliptical valves with slightly pronounced poles and conspicuous combination of other features, such as radial pattern of coarsely punctate uniseriate striae, bowtie-shaped central area without of isolated stigma, and raphe branches with heteromorphous terminal fissures. Ultrastructurally, P. mologaensis shows external areolar openings placed in depressions, which vary markedly in shape from round to slit-like. The new species is compared with similar and misidentified species and distributional data are provided based on confirmed records from the Pleistocene of the Boreal regions of Europe.